The Existence of Gampong in the Middle of Changing Community - Mahmuddin, Mahmuddin; Kolopaking, Laura M; Kinseng, Rilus A; Wasistiono, Sadu; Saharuddin, Saharuddin (Universitas Negeri Semarang, 2016)
The passage of Act No. 18, 2001 on regional autonomy and followed up with the issuance of Qanun No. 4, 2003 on mukim, and Qanun No. 5, 2003 on gampong and reinforced by UUPA No. 11, 2006 on Acehnese government is a history of social identity of Acehnese society, which has been neglected during the conflict. The regional government has made some breakthroughs and one of the breakthroughs was gampong revitalization through a program called âback to gampongâ. The study aims to answer the dynamic of revitalization of gampong institution in the middle of special autonomy implementation and the implementation of Qanun gampong in the administration of gampong institution. The study shows that the implementation of program âback to gampongâ encourages the strengthening process of gampong institution as well as weakens the institution itself. The development of gampong that focuses on physical aspect has created coordination gap among officials of gampong institution in planning system and financial management. Â The tug in the mechanism of financial development and management at gampong has created a space for the involvement and influence from gampong elite in gampong governance. Non-uniform honorary allocation for gampong governmental apparatus is one of indicators of weak role and function of gampong cultural institution because the previous inherent communal values have been calculated economically.